Caracterización de la población de gatos en viviendas de la ciudad de Viña del Mar, Chile - Morales, María A.; Ibarra, Luis; Varas, Cristián (Avances en Ciencias Veterinarias, 2006)
In order to know some demographic characteristics of cat population in Viña del Mar a questionnaire survey was done to a sample of dwellings of the city.A total population size of 43,951 cats with confidence limits (95%) of 36,149 and 51,762 was estimated.Only 33% of dwellings had cats with and average of 0,42 cats by dwelling.The human to cat ratio was 9.3:1, the sex ratio was 88 males by 100 females. The mean age was 2 years and 7 months, more than 50% of the population was 2 years or younger.The principal reasons to keep a cat was for companion and rat control.